PENAGIHAN HUTANG DENGAN PENYEBARAN DATA DIRI DI MEDIA SOSIAL DITINJAU DARI UNDANG-UNDANG NOMOR 11 TAHUN 2008 - Kelung, Noviane H. (Program Studi Ilmu Hukum Universtitas Muhammadiyah Gorontalo, 2025)
In today's digital era, as technology develops, social media also grows very rapidly. Social media as a forum for social communities to interact with each other easily and expand relationships between fellow communities has a very important role in the development of social life in a country in various fields. In his book entitled Social Media: Communication, Cultural and Sociotechnological Perspectives, Rulli Nasrullah explains that social media is an internet-based interaction platform that allows its users to represent themselves and interact with each other as well as work together and share information and communicate with other users. which ultimately forms virtual social bonds. From this definition we can understand the functions and benefits of social media, apart from that social media is also a medium for entertainment, a place to express creativity, a place to channel hobbies, to get various kinds of information quickly, as a place to increase knowledge, and can be used as a source of income by all the features available on social media and of course there are many more benefits from social media.